Inventor networks in emerging key technologies: Information technology vs. semiconductors - Holger Graf (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
We analyze the development of the German knowledge base measured by co-classifications of patents by German inventors and relate this technological development to changes in the structure of the underlying inventor networks. Our central hypothesis states that technologies which become more central to the knowledge base are also characterized by a higher connectedness of the inventor network. We exemplify our theoretical considerations in a comparative study of two patenting fields - information technology and semiconductors. It turns out that information technology shows the highest increases in patents but shows no of a key technology. Contrary, semiconductors develops towards a key technology, despite a moderate increase in the number of patents. The dynamic analysis of inventor networks in both fields shows an increasing connectedness and the emergence of a large component in semiconductors but not in information technology, which is in line with our expectations.
Keywords: O31; Z13; 330; Knowledge relatedness; Innovator networks; Interdisciplinary research; Patents; Key Technology; Wissen; Wissenstransfer; Erfindung; Soziales Netzwerk; Patentrecht; Schlüsselsektor; Informationstechnik; Halbleiter; Deutschland